Types of urethral stricture and their recurrence rates post urological treatments - Basaif, Wedyan Salem; Alamri, Husam Hamad; Mousa, Hind Waleed; Alsayed, Raghad Abdulelah; Almohammadi, Abdullah Mohammed; Altulayqi, Waleed Hamed; Albejawi, Abdulrahman Mohammed; Allam, Ammar Abdullah; Alnamlah, Suliman Abdulrahman; Alghamdi, Mohammed Siraj; Mahrous, Sarah Mohammed (International Journal Of Community Medicine And Public Health, 2021)
Urethral strictures can significantly impact the quality of life for patients because it can be associated with significant complications such as fistulas, bladder calculi, infections and sepsis. Additionally, it might even lead to renal failure. The worldwide prevalence of urethral strictures is high, with an estimated rate of 229-627 patients per 100,000 population. In this literature review, the aim was to discuss the types and etiology of urethral strictures and the recurrence rates following the different management modalities. Studies that were included in this review were published between January 2005 until May 2021. The results support the current evidence that the idiopathic and iatrogenic bulbar strictures are the most common types while penile strictures, the iatrogenic and inflammatory are the most common causes. Recurrence rates are reported after management with almost all of the current management modalities, indicating the need for better interventions to enhance the outcomes and alleviate the quality of care. The recurrence rate of strictures after treatment with internal urethrotomy and direct vision internal urethrotomy by three years is 65%. Other studies reported that the rate of recurrence was estimated to be around 14 after 6 months from internal urethrotomy and up to 27% after 12 months. The rate of complications and recurrence following treatment with anastomotic urethroplasty was estimated to be less than 5%. Detailed information and discussion were provided in the study manuscript.